A Comparative Study of Laparoscopic Appendectomy with Open Appendectomy at a Tertiary Care Hospital - Koirala, Ashok; Gautam, Manish; Shah, Sachidanand; Adhikari, Dinesh; Bhattarai, Amit; Kumar Yadav, Ajay (Journal of Nobel Medical College, 2022)
Background: Appendectomy is most common surgical procedure done for treatment of acute appendicitis. Both laparoscopic and open techniques are used for its removal. The aim of this study is to compare the outcome of laparoscopic appendectomy with open appendectomy. Materials and Methods: A retrospective study was conducted in Nobel Medical College And Teaching Hospital, Biratnagar, Nepal from April 2019 to February 2021.Total 90 patients were enrolled in the study of which 44 in laparoscopic appendectomy group and 46 in open appendectomy group. These two groups were compared for demographic profiles, operative time, postoperative pain, length of hospital stay and surgical site infections. Results: Ninety patients underwent appendectomy of which 44 were in Laparoscopic group and 46 in Open group with similar demographic profiles. The mean operative time in Laparoscopic group was 42.95±2.46 minutes where as in Open group it was 35.25±1.87 minutes [p<0.001].The mean postoperative pain at 8 hours in Laparoscopic group was 7.77±1.03 and in Open group 8.45±1.16 [p=0.002], at day one Laparoscopic group 5.01±0.88 and in Open group 5.80±0.99 [p<0.001],at day two Laparoscopic group 3.54 ±1.19 and in Open group 4.26±0.89[p<0.001]. Mean duration of hospital stay in Laparoscopic group was 2.02±0.26 and Open group was 2.52 ±0.54[p<0.001]. Surgical site infections was noted 1(2.27%) in Laparoscopic group and 6(13.04%) in Open group[p=0.029]. Conclusion: Laparoscopic appendectomy offers less postoperative pain, shorter hospital stay, less surgical site infections but prolonged operative time compared to open appendectomy.